2002
DOI: 10.1017/s0021859602002447
|View full text |Cite
|
Sign up to set email alerts
|

Solution culture for screening rice varieties for sodicity tolerance

Abstract: Sodic soils are widespread, especially in the Indo–Gangetic plain. Amelioration with gypsum is effective, especially when combined with growing a crop of rice. However, it has proved difficult to generate new varieties of sodic-tolerant rice, because of the difficulties of screening – other than in the field, where spatial variation of sodicity is notoriously high. Growing plants at high pH in solution culture in a controlled environment is problematic, because of the effects of pH on nutrient availability. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…At entry level, plant roots experience salt stress when Na + and Cl – along with other cations are present in the soil in varying levels. Ion uptake depends upon the plant growth stage, genotype, temperature, RH and light intensity ( Singh et al, 2002 ). Salt in excessive amount retards plant growth, decrease yield and may cause plant death ( Garciadeblás et al, 2003 ).…”
Section: Salinitymentioning
confidence: 99%
“…At entry level, plant roots experience salt stress when Na + and Cl – along with other cations are present in the soil in varying levels. Ion uptake depends upon the plant growth stage, genotype, temperature, RH and light intensity ( Singh et al, 2002 ). Salt in excessive amount retards plant growth, decrease yield and may cause plant death ( Garciadeblás et al, 2003 ).…”
Section: Salinitymentioning
confidence: 99%
“…Preliminary tests showed that a 0.1% agar solution more effectively simulated the situation in waterlogged soils and in the rhizosphere, as compared to N 2 flushed or non-flushed agar-free nutrient solutions (see also Wetson, 2008). We recognise that there may be a contrast with plants growing in natural saltmarsh soils, but attempting to grow plants at a high pH with hydroponics, means that many micronutrients precipitate from solution, so that the solution has to be changed daily or other ways found of supplying micronutrients, such as by foliar spray (Singh et al, 2002). Experiments were also conducted in a medium based on a natural salt-marsh soil for comparative purposes (see below).…”
Section: Plant Growthmentioning
confidence: 99%
“…The presence of genetic variability for tolerance to acidity (Camargo et al 1995;Foy 1996), salinity (Munns et al 2000;Munns and James 2003), sodicity (Rao et al 2008;Singh et al 2002), toxic soils (Hasnain et al 2011;Yau and Erskine 2000), nutrient use efficiency (Parentoni et al 2010;Zhang et al 2009) and waterlogging tolerance (Cornelious et al 2005;Saqib et al 2013) has been confirmed across different crops at both inter-and intraspecies levels. Past studies identified a wide range of variations to the corresponding soil condition based on traits including shoot growth, symptoms of toxicities and deficiencies and various physiological parameters such as leaf elongation rate, relative growth rate, tissue ion concentrations, etc., and by comparing differential response of genotypes in terms of plant biomass and grain yield under low fertile and low input soil conditions with the normal soil conditions (Table 9.1).…”
Section: Occurrence Of Genetic Variability For Problem Soilsmentioning
confidence: 96%